2022
DOI: 10.1002/advs.202201034
|View full text |Cite
|
Sign up to set email alerts
|

Gestational Leucylation Suppresses Embryonic T‐Box Transcription Factor 5 Signal and Causes Congenital Heart Disease

Abstract: Dysregulated maternal nutrition, such as vitamin deficiencies and excessive levels of glucose and fatty acids, increases the risk for congenital heart disease (CHD) in the offspring. However, the association between maternal amino-acid levels and CHD is unclear. Here, it is shown that increased leucine levels in maternal plasma during the first trimester are associated with elevated CHD risk in the offspring. High levels of maternal leucine increase embryonic lysine-leucylation (K-Leu), which is catalyzed by l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 54 publications
0
20
0
Order By: Relevance
“…There is a lot of evidence showed that, ROS leads to the production and progression of tissue damage in MS and stimulating the Nrf2 pathway may be a protecting mechanism in MS’ pathogenesis ( Ohl et al, 2016 ). Some studies suggest that OS biomarkers such as 8-iso-PGF2 α, AOPPs, IsoP, clusterin, isoprostanes, and 4-HNE increased in MS patients ( Sbardella et al, 2013 ; Guan et al, 2015 ; Zhang et al, 2022 ).…”
Section: The Role Of Os the Neurodegenerative Diseases And The Protec...mentioning
confidence: 99%
“…There is a lot of evidence showed that, ROS leads to the production and progression of tissue damage in MS and stimulating the Nrf2 pathway may be a protecting mechanism in MS’ pathogenesis ( Ohl et al, 2016 ). Some studies suggest that OS biomarkers such as 8-iso-PGF2 α, AOPPs, IsoP, clusterin, isoprostanes, and 4-HNE increased in MS patients ( Sbardella et al, 2013 ; Guan et al, 2015 ; Zhang et al, 2022 ).…”
Section: The Role Of Os the Neurodegenerative Diseases And The Protec...mentioning
confidence: 99%
“…Computer simulations have been widely used for the simulation of biomechanical devices [26][27][28][29][30][31][32] . Due inaccessibility, this technique is the best option for analysis of the blood hemodynamic [33][34][35][36][37][38][39][40] . This The grid generation is also required for the control volume approach [41][42][43][44][45][46][47][48][49] .…”
Section: Applied Technique For Modellingmentioning
confidence: 99%
“…Species of this genus are Gram-negative intracellular facultative pathogens. Brucellosis is characterized as an acute fever illness [ 2 ], associated with various symptoms in humans such as liver and spleen disorders, reproductive abnormalities, neurological problems, and heart-related problems, and also have been classified as a potential bioterrorism agent [ 3 , 4 , 5 ]. Brucellosis remains endemic in various emerging countries in Asia, Africa, Middle East, and South America, where screening of livestock and vaccination fails to control and exterminate the disease [ 6 ].…”
Section: Introductionmentioning
confidence: 99%